Complex forms and replicative intermediates of mitochondrial DNA in tissues from adult and senescent mice. - Pikó, L (1977)
The occurrence and types of complex forms and replicative intermediates of mitochondrial DNA (mtDNA) were investigated in tissues from C57BL/6J mice aged 10-11 months or 29-30 months. Total mtDNA from brain, heart, kidney and liver was isolated in ethidium bromide-CsCl gradients and examined by electron microscopy after aqueous or formamide spreading. Contour length measurements indicated no difference in the monomer size of mtDNA according to either tissue or donor age. The frequencies of catenated mtDNA, ranging from 4 to 8%, varied significantly according to tissue but changed relatively little as a result of donor age. The main age-related effect observed in this study was a significant increase in the frequency of circular dimers, from about 0.05% in adult tissues to 0.3% in kidney, 0.5% in liver, 0.6% in heart and 1.9% in brain of senescent mice. The frequency of D-loop DNA varied from 30 to 60% and that of larger replicative intermediates from 1 to 10%, suggesting differences in the rate of mtDNA replication according to tissue. The frequencies and types of the various replicative intermediates were unaffected by donor age.